Bigger than sports: Identity politics, Colin Kaepernick, and concession making in #BoycottNike. (January 2021) - Eschmann, Rob; Groshek, Jacob; Li, Senhao; Toraif, Noor; Thompson, Julian G.
Abstract: A considerable amount of research has explored echo chambers, or the propensity for online discussions to reflect the same views of individual users, and the online disinhibition effect, which helps to explain the tendency for online discussions to become hostile. Less work has been done to examine instances in online messaging or discussions where social media users signal a willingness to consider or accept a competing point of view. In this study we address this gap using a mixed-methods approach to investigate concession making, or users demonstrating a willingness to adjust their position on a contentious political issue. As a case study, we engage over 2 million tweets related to Colin Kaepernick, a football player who knelt during the national anthem as a form of protest. Here, we build upon the intersection of filter bubbles and online disinhibition effects to make a unique contribution to literature of not only communication about sports and race but contentious issues on social media more broadly. Highlights: Little research explores whether & how social media users accept alternative points of view. Colin Kaepernick is a former NFL player who protests police violence against Black people. We use tweets about Kaepernick to identify 'concessions, ' or users rethinking their point of view. We engage 2 million + tweets and identify user and usage characteristics related to concessions. We discuss these results in light of protests against police brutality against Black people in 2020.